Research in organizational change and development. vol. 30 - Noumair, Debra A.; Shani, Abraham B. Rami; Zandee, Danielle P. (Emerald Publishing Limited, 2023)
Volume 30 of Research in Organizational Change and Development includes seven contributions from leading colleagues around the globe. Taken together they address some key questions for our field: Who do we need to be as OD&C to help create a better world and under what relational conditions can we do such work? What research and theorizing do we have available, and what thought-action repertoires need further development? What robust OD&C methods do we have, and which new methods are needed to be truly helpful in the creation of a better world together? The chapters for this volume are written by senior scholars in the field of OD&C who share their insights from a long-lived, continuous engagement with both theory and practice. This shows in their expansive time horizon when reflecting on the field and how they personally navigated through it. Their seniority also shows in their commitment to help bring the field forward whilst trusting that others may appreciate and continue their legacy. Most of all, and especially endearing in current times, the authors show the joy and strength of collaboration with kindred spirits in inquiry, learning and writing.
Keywords: Organizational change -- Research.; Business & Economics -- Organizational Development.; Organizational theory & behaviour.; elektronické knihy; electronic books